MEASURING FINANCIAL INCLUSION IN SMES: A PATHWAY TO STRENGTHENING FINANCIAL RESILIENCE - Gusi Putu Lestara Permana; I Putu Bayu Andre Wicaksana; Nur Jannah Mohaidin (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
Financing is vital to business performance because it secures funds for projects and operations. For Small and Medium Enterprises (SMEs), access to credit is constrained by weak collateral and limited credit histories. This study examines how financial literacy, behavior, risk, and financial technology affect financial inclusion among SMEs in Gianyar Regency, Bali. Using a quantitative design, we purposively sampled 100 SMEs based on location, fintech adoption, and operating history. Data were collected via a questionnaire and analyzed with SmartPLS 4 using PLS-SEM. Results indicate financial knowledge, behavior, risk management, and fintech enhance inclusion, but risk hinders fintech adoption. These findings highlight that financial competence and risk mitigation are crucial to accessing formal financial services. Integrating Financial Inclusion Theory and Financial Resilience Theory, it argues that fintech adoption can strengthen SMEs’ financial stability. Policymakers and financial institutions should advance financial literacy, prudent conduct, and risk reduction to build more inclusive ecosystems.